2011
DOI: 10.1111/j.1365-2621.2010.02523.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of microwave freeze drying and microwave vacuum drying upon the process and quality characteristics of potato/banana re‐structured chips

Abstract: This study investigated the drying characteristics of microwave freeze-drying (MFD) ⁄ microwave vacuum drying (MVD) of banana ⁄ potato restructured chips of varying proportion and microwave power. The results showed the MFD drying time had a maximum one-hour time difference between the samples treated with 2 W g )1 and 3 W g )1 microwave power; and the higher potato content samples have about 30 min predominance than low potato content samples in drying time and the total drying time of MVD samples was less th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 24 publications
3
13
2
Order By: Relevance
“…of the partially dried product, and equilibrium temperature of 90 ∘ C, respectively. This was in accordance with the results of Jiang et al [30] who reported that higher crispness of the dried products was obtained by adding higher amount of potato in the sample. In Table 3, the interaction terms of all the process parameters showed significantly negative effects ( < 0.01), while the linear terms and quadratic terms of all the process parameters exhibited no significance on hardness.…”
Section: Effect Of Processing Variables On the Hardness Andsupporting
confidence: 93%
“…of the partially dried product, and equilibrium temperature of 90 ∘ C, respectively. This was in accordance with the results of Jiang et al [30] who reported that higher crispness of the dried products was obtained by adding higher amount of potato in the sample. In Table 3, the interaction terms of all the process parameters showed significantly negative effects ( < 0.01), while the linear terms and quadratic terms of all the process parameters exhibited no significance on hardness.…”
Section: Effect Of Processing Variables On the Hardness Andsupporting
confidence: 93%
“…This was probably due to the lowered water content resulting in a decrease in the dielectric constant ϵ ′ and dielectric loss factor ϵ ″. Also, the final drying stage involves removal of sorbed water, and this period can be as long as or longer than the time required for the removal of free water in the initial drying stage . Similar results were found by Mothibe et al At the same microwave power level, the drying time required to achieve the desired moisture content for PSMVD was longer than that in MVD, which was probably due to the fact that the second drying stage with pulsed‐spouted flushing air resulted in destruction of the vacuum environment and loss of heat in PSMVD.…”
Section: Results and Discussionsupporting
confidence: 65%
“…When high power values are used, drying takes place in a much shorter time and the color obtained is more desirable. [29] This is different from the result of Jiang et al, [30] who reported that potato= banana restructured chips became darker as the microwave power was increased. Some researchers have shown that the microwave power used in drying prevents color damage.…”
Section: Texturecontrasting
confidence: 47%